Performance analysis for the improved linear multiuser detectors in BPSK-modulated DS-CDMA systems. - Buzzi, S.
Recently, a new class of linear multiuser receivers for direct-sequence code-division multiple-access (CDMA) systems employing binary phase-shift keying modulation has been introduced. Unlike classical decorrelating and minimum mean-square error linear multiuser detectors, the new receivers exploit the information contained in the pseudo-autocorrelation of the observables, and are, thus, capable of achieving much better performance. We present new results on the performance analysis of this class of new receivers. In particular, with reference to a CDMA system with deterministic spreading codes, we show that the new receivers outperform the classical ones in terms of both error probability and near-far resistance. With regard, instead, to CDMA systems with random spreading, we compute the average system near-far resistance, showing that the new receivers can accommodate twice the number of users accommodated by the classical linear multiuser receivers.
Keywords: BPSK; DS-CDMA systems; MMSE detectors; Binary phase-shift keying modulation; Decorrelating detectors; Deterministic spreading codes; Direct-sequence code-division multiple-access.; Error probability; Linear detectors; Minimum mean-square error detectors; Multiuser detectors; Near-far resistance; Pseudo-autocorrelation.; Pseudoautocorrelation; Random spreading